The little engine that could - Piper, Watty (Platt & Munk, Pblishers, an imprint of Grosset & Dunlap, 2020)
The kindness and determination of the Little Blue Engine have inspired millions of children around the world since the story was first published in 1930. Cherished by readers for ninety years, The Little Engine That Could is a classic tale of a little engine that, despite her size, triumphantly pulls a train full of wonderful things to the children waiting on the other side of a mountain.